Central banks, trade unions and reputation - is there room for an expansionist manoeuvre in the European Union? - Toralf Pusch; Arne Heise (Universität Hamburg, Department Wirtschaft und Politik, 2008)
It is now a few years since the introduction of the common currency, and Europe is still experiencing high unemployment. The conventional logic attributes this problem to strong trade unions and other flaws in the labour market. This article takes a different approach. Using a game theoretic model we look at the changes that occur if trade unions and the central bank have different options to choose from in a climate of uncertainty. In a singlestage game the most probable outcome is a high unemployment rate as high as the NAIRU. However, there is also a slight chance that a central bank might take the risk associated with employment expansion (if trade unions cooperate the risk pays off). Moreover, results change dramatically if the game is repeated. This allows for effects on the trade union's reputation. It can be shown that this, in turn, improves the likelihood of employment expansion.
Keywords: C72; E12; E24; E58; J51; 300; Monetary Policy; labour unions; reputation building; employment; EMU; Geldpolitik; Lohnpolitik; Europäische Wirtschafts- und Währungsunion; Wiederholte Spiele; Reputation; Gewerkschaft; Vollbeschäftigung; Inflationsbekämpfung; Theorie; EU-Staaten